Scalable simultaneous multiqubit readout with 99.99% single-shot fidelity - Burrell, A; Szwer, D; Webster, S; Lucas, D (2010)
We describe single-shot readout of a trapped-ion multiqubit register using space- and time-resolved camera detection. For a single qubit we measure 0.9(3)×10-4 readout error in 400μs exposure time, limited by the qubit's decay lifetime. For a four-qubit register (a "qunybble"), we measure an additional error of only 0.1(1)×10-4 per qubit, despite the presence of 4% optical cross-talk between neighboring qubits. A study of the cross-talk indicates that the method would scale with a negligible loss of fidelity to 10000 qubits at a density of 1 qubit/μm2, with a readout time of 1μs/qubit. © 2010 The American Physical Society.